The analysis of the chemical composition of the grape seed oil and peel - Sergheev, Liliana (Acta et Commentationes Exact and Natural Sciences, 2023)
The increased interest in grapevines and their products, which are universal in terms of taste and healing properties, results from the diverse content of beneficial compounds that have a positive effect on the human body. The valuable chemical composition of grape seed oil, as well as the peel of both white and red grape varieties, supports the importance of using this product not only in food but also in other areas.